La estación de la Sabana como nodo urbano y renovador del espacio público en el barrio el Listón. - Ramírez Ledezma, Juan David (Universidad Antonio Nariño, 2023)
The topic to be investigated is the recovery of public spaces through urban renewal in the historic center of Bogotá, for which a specific area is chosen to analyze, which is on 19th street with diagonal 19th corresponding to the Sabana station, town of the martyr’s neighborhood el Listón.